Restarting elective orthopaedic services during the COVID-19 pandemic: Do patients want to have surgery?. (June 2020) - Chang, J.; Wignadasan, W.; Kontoghiorghe, C.; Kayani, B.; Singh, S.; Plastow, R.; Magan, A.; Haddad, F.
No abstract available